Pembelajaran Flipped Classroom Konten E learning - I Putu Suardipa; I Made Sedana; Ni Nyoman Lisna Handayani (STAHN Mpu Kuturan Singaraja, 2022)
In addition to adopting the bloom taxonomic system that was reversed in the initial process, flipped classroom also adopted blended learning strategies. In flipped classroom learning that uses blended learning strategies that contain the meaning of mixing elements, or combining one pattern with another pattern. Blended learning is a variety of e-learning strategies based on e-learning. In flip classroom itself blended learning in question is a mixture of several strategies, such as: (1) face to face learning; (2) m-learning; (3) project base learning; (4) problem base learning; (5) peer learning; (6) individualized learning, and (7) group learning. Implementing the flip classroom learning model in e learning needs to be understood that there are two stages, namely the out class and in class stages.